Professional interaction in management of the triad: Permanent Education in Health, patient safety and quality - Cintia Koerich; Alacoque Lorenzini Erdmann; Gabriela Marcellino de Melo Lanzoni (Universidade de São Paulo, 2020)
Objective: to understand how professional interaction takes place in the hospital organizational structure for the management of Permanent Education in Health, to guarantee patient safety and the quality of nursing care. Method: this is a qualitative study, which used the structuralist aspect of the Grounded Theory as a methodological framework. 27 interviewers participated in the study, who made up four sample groups. Results: six categories and 13 subcategories were presented, representing the studied phenomenon and highlighting particularities of the public health system and the influence of the manager's support and management priority, the disposition of the organizational structure, the institutional culture, the external encouragement to institution, and the nurses' initiative and leadership in the professional interaction for the management of the Permanent Education in Health, patient safety, and quality of care triad, revealing the need for cultural change through interdisciplinarity. Conclusion: the professional interaction in the hospital organizational structure requires the creation of new management models with an emphasis on more participative management, in order to improve the care processes in hospital institutions.